Live Streaming and Digital Stages for the Hungry Ghosts and Deities - Lim, Alvin Eng Hui (Religions, 2020)
Many Chinese temples in Singapore provide live streaming of getai (English: a stage for songs) during the Hungry Ghost Month as well as deities’ birthday celebrations and spirit possessions—a recent phenomenon. For instance, Sheng Hong Temple launched its own app in 2018, as part of a digital turn that culminated in a series of live streaming events during the temple’s 100-year anniversary celebrations. Deities’ visits to the temple from mainland China and Taiwan were also live-streamed, a feature that was already a part of the Taichung Mazu Festival in Taiwan. Initially streamed on RINGS.TV, an app available on Android and Apple iOS, live videos of getai performances can now be found on the more sustainable platform of Facebook Live. These videos are hosted on Facebook Pages, such as “Singapore Getai Supporter” (which is listed as a “secret” group), “Singapore Getai Fans Page”, “Lixin Fan Page”, and “LEX-S Watch Live Channel”. These pages are mainly initiated and supported by LEX(S) Entertainment Productions, one of the largest entertainment companies running and organising getai performances in Singapore. This paper critically examines this digital turn and the use of digital technology, where both deities and spirits are made available to digital transmissions, performing to the digital camera in ways that alter the performative aspects of religious festivals and processions. In direct ways, the performance stage extends to the digital platform, where getai hosts, singers, and spirit mediums have become increasingly conscious that they now have a virtual presence that exceeds the live event.